Da génese de lugar do projecto: uma biblioteca para Pispala - David Fernando Gonçalves Monteiro (2015)
This work aims at clarifying the design process of a design exercise for a Library in Pispala, Finland. Highlighting the thematic variety and the methodologies used in this design process, this project was developed during an exchange period of eight months at the Tampere University of Technology, in Finland, as part of the course of Architectural Design Studio subject. Through the thematic influence of a professional experience at Herzog & de Meuron's studio, the essay lays on the relationship between the land's condition and the proposed program, towards an interpretation focus on the process of projecting a library for the singularity of a Finnish landscape.